Continuous Integration (CI) with Jenkins using plugins : learn how to discover, install, update, and manage Jenkins plugins - Bowersox, Kevin (O'Reilly Media, 2017)
"Plugins enhance the capabilities of the Jenkins automation server, making it possible for developers to refine their approach to building, deploying, and automating their Jenkins projects. The Jenkins plugins index is a library of over 1,000 plugins; this course shows you how to choose the best ones for your needs. You'll learn how to use the Jenkins plugin manager to install, update, and remove plugins. Then, as a bonus, you'll become familiar with five of the most popular Jenkins plugins in use today."--Resource description page.